돼지 MC4R 유전자 892G>A 다형성이 비육돈의 도체형질에 미치는 영향 - 한상현; 이성수; 고문석; 성필남; 박범영; 조인철; Han, S.H; Lee, S.S; Ko, M.S; Seong, P.N; Park, B.Y; Cho, I.C (Journal of animal science and technology, 2007)
receptor(MC4R) gene and carcass traits was examined in randomly selected commercial pigs. A porcine MC4R gene was genotyped for Asp298Asn(nt. 892G>A) by polymerase chain reaction-restriction fragment length polymorphism(PCR-RFLP). A total of three genotypes, A/A, A/G, and G/G, were found with 28.8, 22.8, and 48.4% frequencies, respectively. In the whole population, pigs containing 892A/- showed significantly higher marbling score than those of homozygotes G/G(P<0.05). Two homozygotes, A/A and G/G showed lower in meat color score but higher in water holding capacity than those of heterozygotes A/G(P<0.01). However, the carcass weight of the barrows containing wild type -/G was significantly higher(i.e. more than 2.5kg) than those of homozygotes A/A(P<0.05). The effects of each genotype on carcass traits in the gilts were similar to those of the whole population, but not in barrows, suggesting an unknown sex-related effect on carcass traits. This study suggested that the genotype MC4R A/- could improve the meat quality in the commercial pig production. However, since the genetic polymorphism of MC4R gene differentially affected the carcass traits in sex-related manner, therefore, both parameters, the sex and genotype, should be considered for marker-assisted selection in commercial pig production. 임의적으로 선정된 비육돈 집단에서 melano- cortin-4 receptor(MC4R) 유전자의 유전적 변이와 도체형질의 연관성을 조사하였다. 돼지 MC4R 유전자형은 Asp298Asn(nt. 892G>A) 돌연변이를 PCR-RFLP 방법으로 결정하였다. 비육돈 집단에서 유전자형 A/A, A/G, G/G가 모두 출현하였고, 빈도는 각각 28.8, 48.4, 22.8%를 나타내었다. 전체 비육돈에서 유전자형 A/-은 G/G에 비해 근내지방도가 유의적으로 높게 나타났다(P<0.05). 동형접합자 A/A와 G/G가 이형접합자 A/G인 도체에 비해 육색도는 더 낮고 수분삼출도는 높은 것으로 확인되었다(P<0.01). 반면, -/G인 거세돈의 도체중이 A/A에 비해 도체중이 유의적으로 무겁게(약 2.5kg) 나타났다(P<0.05). 각 유전자형의 도체형질에 대한 효과는 미경산돈에서는 전체 비육돈 집단에 대한 효과와 유사하나, 거세돈 집단과는 다소 차이가 있었고, 이는 도체형질에 대한 현재까지 알려지지 않은 성-관련 효과로 추정된다. 본 연구에서 비육돈 생산에 있어 MC4R A/- 유전자형이 육질을 향상시킬 수 있을 것으로 기대된다. 하지만, MC4R 유전자형들이 성과 관련되어 차별적으로 도체형질에 영향을 주고 있기 때문에, 비육돈 생산을 위한 marker-assisted selection을 위해서는 성과 유전자형 모두가 고려되어져야 할 것이다.